The Development of Listening and Speaking Skills in Third-Year Elementary Students Using Plicker Games - ชาติมนตรี ณัฎฐณิชา; รอดเส็ม พัชราพรรณ; เหลือคลังทอง อภิญาน์รัชน์; คงคาชาติ สุดารัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this study were to: (1) investigate the development of English listening skills among Grade 3 students before and after receiving instruction through the use of the Plickers game, and (2) investigate the development of English speaking skills among Grade 3 students before and after receiving instruction through the use of the Plickers game. The target group consisted of 20 third-grade students from Samchai Wittaya School, selected through purposive sampling. The research instruments included (1) lesson plans using the Plickers game, (2) an English listening skills test, and (3) an English speaking skills test. The statistical methods used for data analysis were mean and standard deviation. The results revealed that: (1) students taught using the Plickers game showed an average increase of 6.30 points in their English listening skills. The pre-test average score was 5.65, with a standard deviation of 1.63, while the post-test average score was 11.95, with a standard deviation of 1.88. Additionally, (2) students taught using the Plickers game showed an average increase of 2.55 points in their English speaking skills. The pre-test average score was 5.45, with a standard deviation of 1.76, while the post-test average score was 8.00, with a standard deviation of 2.34.